FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN LOW BACK PAIN PADA PETANI JERUK DI DESA DOKAN KECAMATAN MEREK KABUPATEN KARO TAHUN 2015 - deli sitepu; Muhammad makmur sinaga; Halinda Sari Lubis (Lingkungan dan Kesehatan Kerja, 2015)
Abstract This study is about the factors associated with complaints of low back pain (LBP) on citrus farmers in the village of Dokan Sub Brand Karo Year 2015. The variables in this study consisted of occupational factors and individual factors. This research is a quantitative research methods and analytical survey with croos sectional design. The number of samples taken with the criteria set by the researchers as much as 32 respondents. The results were obtained by interviews with questionnaires Nordic Body Map. The aim of research to determine the factors associated with complaints of low back pain in citrus farmers in the village of Dokan Sub Brand Karo 2015. Variable factors associated with the occurrence of work complaints of low back pain is the type of work to lift the p value 0.010 and the type of work to spray with p value 0.042. Variable individual factors associated with low back pain complaints that tenure with p value 0.016, sex with p value 0.004, and smoking with p value 0.032. Suggested to citrus growers to do stretching or warming up before and after the occupation, farmers should also resting when it is pain in the lower back and adjust the limits of the back according to age and the load to be lifted, to reduce pain in the lower back .